Pemberdayaan Masyarakat Melalui Budidaya Jamur Tiram Berbasis Digital Marketing di Desa Imbanagara - Angga Nugraha; Ergun Alfauzi; Muhamad Yuda Noor Akbari; Ii Sujai; Irfan Nursetiawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Optimization of community empowerment through mushroom cultivation has a major problem, namely the lack of implementation of digital marketing strategies in oyster mushroom cultivation to increase market access, sales efficiency, and production capacity. With the implementation of digital marketing strategies, the Sukahurip II Farmer Group can promote their products more widely, effectively, reach a larger market and increase sales. The methods used include training and assistance in the use of digital platforms such as social media, e-commerce, and online marketing applications. The results of this implementation show that with the support of digital marketing, the community is able to increase income, expand customer networks, and strengthen their position in the market. This study provides practical guidance for the implementation of digital marketing strategies in oyster mushroom cultivation businesses, as well as providing recommendations for the development of similar empowerment models in other sectors.